ANALISIS PERUBAHAN TUTUPAN LAHAN HUTAN DI IUPHHK-HA PT. GEMA HUTAN LESTARI KABUPATEN BURU PROVINSI MALUKU - Ibnu R Pattilouw; G Mardiatmoko; Ferad Puturuhu (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2019)
The objectives of this study are: identifying land cover, analyzing land cover change, calculating the rate of forest degradation and deforestation, and determining forest management policies. This research was conducted using remote sensing methods and GIS for obtaining land cover change data for several years and conducting mapping. From the research conducted, the results of the classification of forest land cover using Landsat 8 OLI / TIRS imagery in 2013, 2016 and 2018 consisted of forests, shrubs, reeds, swamps, rivers and open land. The highest land cover change that occurred in 2013 up to 2016 covered forests turned into open land amounting to 12261.75 ha. Shrubs into open land also experienced a large change of 12912.25 ha. Forests that have been degraded since 2013-2016 covering an area of ​​17703.07 ha,